Bladder cancer: smoking, beverages and artificial sweeteners - Morgan, Robert W. (1974)
A matched patient-control study of bladder cancer examined the relationship of the disease to occupation, smoking and intake of tea, coffee, cola, alcohol and artificial sweeteners. There was no association of disease with occupation for these patients. Heavy smoking gave relative risks of 6.37 and 4.36 for men and women respectively; there was evidence of a dose-response relationship. Tea and coffee intake did not increase the risk of disease nor did prolonged use of artificial sweeteners. Alcohol and cola intake increased the relative risk of bladder cancer among male smokers. There is some suggestion that smoking interacts with both alcohol and cola intake in the production of bladder cancer.